DOMINANCE, ASSOCIATION AND DISTRIBUTION PATTERN OF TREE SPECIES IN BURNT FOREST IN EAST KALIMANTAN - Subekti Rahayu (SEAMEO BIOTROP, 2021)
Repeated forest fires remarkably impact species composition. Pioneer species colonize the burnt forest and widely develop up to 30 years after a fire, but late-succession species regenerate gradually or even disappear owing to direct impact of fires or other ecological consequences related to fires. Hence, forest restoration through assisted natural regeneration needs some information about the state of post-fire species composition. To better evaluate tree species composition after repeated fires, the species dominance as an indicator of species composition was used in this research, with additional information on the species association and distribution patterns. A 1.8-hectare plot, divided into 180 subplots with a size of 10 × 10 m, was established in a secondary forest in Samboja Research Forest, East Kalimantan. The sample plot was burnt in 1982/1983 and 1997/1998. All trees above 10 cm DBH were measured and leaf specimens were collected for species identification at the Herbarium Bogoriense, Cibinong, West Java. For comparison, the 1981 data from the Indonesian Institute of Sciences were used. Analysis of the Importance Value Index used the species dominance data. A 2 × 2 matrix based on the presence–absence of species for each subplot was used to analyze the association index among species. Variance and average value ratio of certain species present in each subplot were expressed in a dispersion index. A chi-square was used to test the significance between the association and dispersion index. Thirteen years after a second fire, pioneer species Macaranga gigantea were most dominant, followed by Vernonia arborea, a sub-climax species. This indicated that the forest was in an early succession process. Pholidocarpus majadum was consistently dominant before and after the fire. A total of 38 pairs of species were significantly positively associated and 4801 pairs negatively associated. About 60% of species association, both negatively and positively, were among the